The Chinese Economic Area Economic Integration without a Free Trade Agreement - Jones, Randall S.. (OECD Economics Department Working Papers, 1992)
This paper describes the de facto economic integration taking place between China, Hong Kong and Taiwan -- the "Chinese Economic Area" -- and analyses basic factors underlying the process. Even in the face of weak economic performance in OECD countries the integration has helped underpin rapid growth in all three economies, particularly in China's south-eastern provinces. If Chinese policies are further liberalised within a reasonably stable macro-environment, the Chinese Economic Area could become a major player in world markets within one generation and require massive adjustment in the rest of the world ...